2018
DOI: 10.16984/saufenbilder.394911
|View full text |Cite
|
Sign up to set email alerts
|

GIS Based Bus Stop Optimisation For Sakarya Public Transportation System

Abstract: In today's world, the needs for transportation have increased and the existing solutions have become insufficient in response to the demand especially with the increase of urban life and the widespread urbanisation. For this reason, local authorities aim to improve urban public transportation services, one of the effective in-city transportation solutions, in order to solve the current needs of transport and reduce or regulate the current traffic intensity. In this study, geographical information system (GIS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Successful urban bus transit systems will increase the demand for public transportation, and enhance city life by reducing the number of people who drive alone. Many urban dwellers attribute traffic jams and pollution, to the frequency with which people utilize their personal cars to get to town [32]. On public transportation networks, it is possible to accommodate high levels of demand for timeand distance-based travel.…”
Section: Performance Of the Public Transportation Systemmentioning
confidence: 99%
“…Successful urban bus transit systems will increase the demand for public transportation, and enhance city life by reducing the number of people who drive alone. Many urban dwellers attribute traffic jams and pollution, to the frequency with which people utilize their personal cars to get to town [32]. On public transportation networks, it is possible to accommodate high levels of demand for timeand distance-based travel.…”
Section: Performance Of the Public Transportation Systemmentioning
confidence: 99%
“…The objective function includes a maximum reduction in operating costs under the appropriate level of public transport services [15]. Furthermore, the objective of several studies has been to maximize social welfare, that is, consumer surplus plus government revenue minus the operating costs of the public transport companies [30,31].…”
Section: Overview Of Solutionsmentioning
confidence: 99%
“…Some academics have found that the walking distance (d w ) of residents around a BRT line to stations determines the probability of choosing BRT, from which the coverage coefficient of bus stops is obtained [31]. Some studies show that residents within 300 meters of a bus station have a higher probability of taking the bus and are more stable, while the probability of taking the bus more than 300 meters gradually decreases [24,27,35,36].…”
Section: Construction Of a Bottom-level Modelmentioning
confidence: 99%
“…The demand for public transport and the quality of life in cities would improve if appropriate plans for urban bus transportation were implemented. This will reduce private car use and significantly reduce traffic congestion in cities [3].…”
Section: Introduction 1overviewmentioning
confidence: 99%